2000
DOI: 10.1598/rrq.35.2.1
|View full text |Cite
|
Sign up to set email alerts
|

3.6 Minutes per Day: The Scarcity of Informational Texts in First Grade

Abstract: S Although scholars have called for greater attention to informational texts in the early grades for some time, there have been few data available about the degree to which informational texts are actually included in early grade classrooms, and in what ways. This study provides basic, descriptive information about informational text experiences offered to children in 20 first‐grade classrooms selected from very low‐ and very high‐SES school districts. Each classroom was visited for four full days over the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
372
2
35

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(430 citation statements)
references
References 21 publications
4
372
2
35
Order By: Relevance
“…This was one of the first studies to challenge the notion that narratives should be the primary type of text structure with young children. The "narratives as primary" idea was also highlighted in a report by Duke (2000), who examined firstgrade classroom libraries and found that narrative books overwhelmingly outnumbered nonfiction texts. This is regrettable, as studies have highlighted the benefits and success of using nonfiction in the early grades (Doiron, 1994;Duthie, 1994;Pappas).…”
Section: Knowledge Of Text Structuresmentioning
confidence: 93%
“…This was one of the first studies to challenge the notion that narratives should be the primary type of text structure with young children. The "narratives as primary" idea was also highlighted in a report by Duke (2000), who examined firstgrade classroom libraries and found that narrative books overwhelmingly outnumbered nonfiction texts. This is regrettable, as studies have highlighted the benefits and success of using nonfiction in the early grades (Doiron, 1994;Duthie, 1994;Pappas).…”
Section: Knowledge Of Text Structuresmentioning
confidence: 93%
“…Van Kleeck (2008) also suggests the use of storybook reading to structure questions that promote cognitively complex responses such as making predictions and inferences. Duke (2000) makes the case for introducing far more informational texts including a wide variety of non-fiction literature that is increasingly available from commercially published sources. These contain the mid-range high utility academic words (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Developing a corpus of these types of words that are visible in children's writing provides an invaluable starting point for considering the 'next words to know' in addressing the learning needs of youngsters who do not otherwise have ready access to them. While teachers increasingly attend to the meanings of topic or subject specific vocabulary (Snow, 2010), they tend to ignore the high utility, general academic vocabulary that travels across curricular boundaries (Duke, 2000;Scott, Jamieson-Noel & Asselin, 2003), and that are central to academic literacy.…”
Section: Anglo-saxon Word Origins Concrete Meaningsmentioning
confidence: 99%
“…In the basic schools, instructional content is by and large skewed towards narrative texts (Duke, 2000). However, as students go through academic progression from basic schools towards senior high and tertiary institutions, they are more and more required to engage with expository texts especially in content areas as science rather than narrative.…”
Section: Statement Of Problemmentioning
confidence: 99%